RESPON PERKECAMBAHAN BEBERAPA KULTIVAR PADI GOGO PADA TEKANAN OSMOSIS PEG (polyethylene glycol) YANG BERBEDA - Irsam, Sakka Samudin, Enny Adelina, Irsam (AGROTEKBIS, 2016)
This research was conducted at the Laboratory of Seed Science and Technology, Faculty of Agriculture, University of Tadulako at the month of March-April 2016, with the aim is to assess the response of germination of some cultivars of upland rice on the different of pressure osmosik PEG (polyethylene glycol) are different, so as to obtain the viability of cultivars of upland rice best. This study was an experimental study compiled by two factors (factorial) using completely randomized design (CRD). The first factor is composed of five different cultivars. The second factor consisted of four treatments PEG 6000 by the difference pressure, ie without PEG = P0, P1 = -1 bar, P2 = -2 bar, and P3 = -3 bar. Thus there will be 16 treatment combinations, and each treatment was replicated four times, so overall there are 64 experimental units. The data were analyzed by analysis of variance (F-Test), if the results of analysis of variance show significant differences, it will be further tested honesnesty significant difference (HSD) at 5%. The results of this study was all the local upland rice varieties still have germinated response until -3 bar osmotic pressure. Tagolu cultivars and Tokalang were higher speed in the germination phase on several different osmotic pressure. Tokalang cultivars are varieties that are tolerant to drought and has the ability to germinate in response to normal even in a state reeling and has the highest average of several variables observation. The application of osmotic pressure in the form of PEG 6000 to -3 bar causing drought stress on the germination phase .